Programs of Russian businesses aimed at employes’ families: A Content analysis based on eps-ratings data - Kobets, Irina; Vasojević, Nena (Sociološki pregled, 2026)
The purpose of this study is to examine the characteristics of corporate family-support programs for employees and their regional specificities. The study was conducted in Russia between April and May 2025. A content analysis of data from the EPS-rating of enterprises (182 enterprises from 48 regions) was conducted. The findings indicate that businesses predominantly implement universal measures, such as one-time financial benefits and corporate events, whereas comprehensive long-term programs are considerably less widespread. The highest levels of engagement are observed in the Central and Volga Federal Districts, with large enterprises demonstrating greater propensity to adopt such practices. These results provide an empirical basis for assessing the current state of corporate demographic policy and for identifying potential avenues for its institutionalization and further development.